Anterior mediastinal Hodgkin lymphoma presenting as an extremely hypervascular tumor on computed tomography: A case report. Issue 19 (May 2018) - Lee, Soo Jeong; Rho, Ji Young; Kim, Gwang Il; Park, Joonsuk
Abstract: Rationale: In the thorax, Hodgkin lymphoma (HL) most frequently involves the anterior mediastinal and paratracheal regions and tends to spread to contiguous nodal groups. Enlarged lymph nodes typically have homogeneous soft tissue attenuation similar to that of muscle tissue on computed tomography (CT). Patient concerns: A contrast-enhanced CT examination of a 19-year-old man with right-sided chest pain showed an intense, heterogeneously enhancing mass with organization of serpentine and dilated blood vessels in the right anterior mediastinum that had invaded the upper lobe of the right lung. Diagnoses: Following a wedge resection, histopathological examination showed Reed-Sternberg cells that were positive for CD-15 and CD-30, which is typical of HL. Interventions: The patient was started treatment with 6 cycles of doxorubicin, bleomycin, vincristine, and dacarbazine (ABVD) regimen. Outcomes: After chemotherapy, the patient had shown a partial response to the treatment. Lessons: This presentation of HL as an extremely hypervascular anterior mediastinal mass on CT imaging has not been previously reported in the literature. This case suggests that HL should be included in the differential diagnosis of a hypervascular anterior mediastinal mass, especially if the patient is a young adult.